Dermoscopy of localized cutaneous nodular amyloidosis resembling granulomatous disorders - Bhavesh Sonagara; Hita Mehta; Prachi Gajjar (Wolters Kluwer Medknow Publications, 2019)
Cutaneous amyloidosis refers to a group of skin diseases, which is characterized by the deposition of amyloid material in the skin. Among them, Localized cutaneous nodular amyloidosis (LCNA) is the rarest type of cutaneous amyloidosis. A 38-year-old male presented to dermatology OPD with a single soft nodular lesion on left cheek. On basis of clinical and dermoscopic examination we thought it as granulomatous disease but histopathologically confirmed diagnosis of LCNA. Systemic amyloidosis is excluded on clinical as well as laboratory bases. The patient was treated with topical tacrolimus with slight improvement and followed up for 1 year and no systemic abnormalities were found.